2012
DOI: 10.1111/j.1478-3231.2012.02830.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators of survival in patients with compensated and decompensated cirrhosis

Abstract: Background/Aims Patients with cirrhosis are classified in a compensated and a decompensated stage. Portal hypertension is responsible for most of the complications of cirrhosis that mark the transition from compensated to decompensated cirrhosis. The objectives of this study were (a) to analyse survival of the different stages and substages of cirrhosis and (b) to examine the prognostic value of the hepatic venous pressure gradient (HVPG) at each of the stages. Methods A total of 729 patients with suspected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
2
12

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(209 citation statements)
references
References 19 publications
14
162
2
12
Order By: Relevance
“…11 Given the difference in risk of mortality and survival rates between compensated and decompensated cirrhosis, patients and health care providers should have a clear understanding of distinctions between the 2 stages. 18,22,23 Other tools for assessing CLD severity and prognosis have been used for decades. The extent of cirrhosis is subclassified into 4 or 5 stages with varying prognoses, each defined clinically by the presence or absence of select complications ( Figure 2).…”
Section: Pathogenesis and Classification Of Cirrhosismentioning
confidence: 99%
“…11 Given the difference in risk of mortality and survival rates between compensated and decompensated cirrhosis, patients and health care providers should have a clear understanding of distinctions between the 2 stages. 18,22,23 Other tools for assessing CLD severity and prognosis have been used for decades. The extent of cirrhosis is subclassified into 4 or 5 stages with varying prognoses, each defined clinically by the presence or absence of select complications ( Figure 2).…”
Section: Pathogenesis and Classification Of Cirrhosismentioning
confidence: 99%
“…In other words, the patient's condition suggests the presence of a certain degree of PH, evidenced by a mean HVPG of 14.9 mmHg and 75.6% patients with HVPG 12 mmHg or higher. In fact, investigators suggested that the link between the severity of PH and the prognosis of cirrhosis patients is contentious, and the influence of portal pressure may depend on the additional patient condition factors such as liver function and/or compensation/decompensation [22,23].…”
Section: Research Articlementioning
confidence: 99%
“…Clinically significative portal hypertension ,CSPH, defined by HVPG above 10 mmHG, is an important predictive factor of decompensation, appearance of hepatocellular carcinoma (HCC), death and also related to therapeutic response (BERZIGOTTI, 2008;ZIPPRICH;GARCIA-TSAO et al, 2012;VOROBIOFF;GROZMANN, 2015). Those patients with a GPVH between 5 mmHg and 10 mmHg, non-clinically significative portal hypertension, should have optimize ethiology treatment to avoid disease progression.…”
Section: Artigos De Revisãomentioning
confidence: 99%